1998
DOI: 10.1128/aac.42.5.1088
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vancomycin-Resistant Enterococcus faecium Isolates from the United States and Their Susceptibility In Vitro to Dalfopristin-Quinupristin

Abstract: In the course of clinical studies with the investigational streptogramin antimicrobial dalfopristin-quinupristin, isolates of vancomycin-resistant Enterococcus faecium were referred to our laboratory from across the United States. Seventy-two percent of the strains were of the VanA type, phenotypically and genotypically, while 28% were of the VanB type. High-level resistance to streptomycin or gentamicin was observed in 86 and 81%, respectively, of the VanA strains but in only 69 and 66%, respectively, of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 31 publications
2
44
0
1
Order By: Relevance
“…Quinupristin/dalfopristin has a broad spectrum of activity in vitro against gram-positive bacteria, including coagulase-negative staphylococci, methicillinsusceptible and methicillin-resistant Staphylococcus aureus, and multidrug-resistant strains of Streptococcus pneumoniae. Quinupristin/dalfopristin is also active against most vancomycinresistant strains of Enterococcus faecium [24,25]. This activity of quinupristin/dalfopristin against vancomycin-resistant E. faecium is generally bacteriostatic and not bactericidal [25].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Quinupristin/dalfopristin has a broad spectrum of activity in vitro against gram-positive bacteria, including coagulase-negative staphylococci, methicillinsusceptible and methicillin-resistant Staphylococcus aureus, and multidrug-resistant strains of Streptococcus pneumoniae. Quinupristin/dalfopristin is also active against most vancomycinresistant strains of Enterococcus faecium [24,25]. This activity of quinupristin/dalfopristin against vancomycin-resistant E. faecium is generally bacteriostatic and not bactericidal [25].…”
mentioning
confidence: 99%
“…Quinupristin/dalfopristin is also active against most vancomycinresistant strains of Enterococcus faecium [24,25]. This activity of quinupristin/dalfopristin against vancomycin-resistant E. faecium is generally bacteriostatic and not bactericidal [25]. Because of the paucity of available antimicrobial agents with proven efficacy for treatment of infections due to vancomycinresistant E. faecium, we evaluated the efficacy and safety of quinupristin/dalfopristin for treatment of serious infections caused by vancomycin-resistant E. faecium.…”
mentioning
confidence: 99%
“…The emergence of enterococci demonstrating high level resistance to a broad range of existing antimicrobials (␤-lactams, aminoglycosides, glycopepetides) as well as newer agents such as quinuspristin-dalfopristin and linezolid [4][5][6][7][8][9] has made bactericidal eradication of these organisms problematic and difficult to achieve. Several drug combinations including the newer agents have been evaluated in vitro and in animal models but results of these have varied, ranging from synergy to ineffectiveness [12][13][14][15][16][17][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have also shown that E. faecalis carries multiple virulence genes whereas E. faecium carries few or no such virulence genes [4]. The significance of enterococcal infections is increasing and vancomycin-resistant enterococci (VRE) as well as resistance to a broad range of antimicrobial agents including recently developed therapeutic agents (such as teicoplanin, quinupristin-dalfopristin (Q-D) and linezolid) are becoming widespread in many parts of the world [4][5][6][7][8][9]. Such infections require a bactericidal therapy, which is usually obtained only with a synergistic combination of a cell wall active agent (such as a penicillin or vancomycin), plus an aminoglycoside [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Other important streptococci, such as Streptococcus pyogenes, Streptococcus agalactiae, and the group C and G streptococci, are also susceptible at achievable quinupristin-dalfopristin concentrations. Quinupristin-dalfopristin shows inhibitory activity against most E. faecium strains with or without expression of high-level vancomycin resistance [31]. Quinupristin-dalfopristin inhibited 86.4% of vancomycin-resistant E. faecium isolates at 1 g/mL and 95.1% at 2 g/mL.…”
Section: Spectrum Of Antimicrobial Activitymentioning
confidence: 97%